2012
DOI: 10.1158/1078-0432.ccr-12-1513
|View full text |Cite
|
Sign up to set email alerts
|

Lurbinectedin (PM01183), a New DNA Minor Groove Binder, Inhibits Growth of Orthotopic Primary Graft of Cisplatin-Resistant Epithelial Ovarian Cancer

Abstract: Purpose: Epithelial ovarian cancer (EOC) is the fifth leading cause of death in women diagnosed with gynecologic malignancies. The low survival rate is because of its advanced-stage diagnosis and either intrinsic or acquired resistance to standard platinum-based chemotherapy. So, the development of effective innovative therapeutic strategies to overcome cisplatin resistance remains a high priority.Experimental Design: To investigate new treatments in in vivo models reproducing EOCs tumor growth, we generated a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 50 publications
2
67
1
Order By: Relevance
“…In this sense, lurbinectedin is able to attenuate the repair of specific nucleotide excision repair (NER) substrates (17,18). In addition to its activity in tumor cells, it was recently shown that lurbinectedin affects the inflammatory microenvironment, with a selective apoptotic-inducing effect on mononuclear phagocytes and a specific inhibition of production of inflammatory cytokines (19,20). In this work, we show that, following its specific target on CG-rich sequences located at promoters of protein-coding genes, lurbinectedin induces the specific degradation of elongating (phosphorylated) RNA polymerase II (Pol II) by the ubiquitin-proteasome machinery.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, lurbinectedin is able to attenuate the repair of specific nucleotide excision repair (NER) substrates (17,18). In addition to its activity in tumor cells, it was recently shown that lurbinectedin affects the inflammatory microenvironment, with a selective apoptotic-inducing effect on mononuclear phagocytes and a specific inhibition of production of inflammatory cytokines (19,20). In this work, we show that, following its specific target on CG-rich sequences located at promoters of protein-coding genes, lurbinectedin induces the specific degradation of elongating (phosphorylated) RNA polymerase II (Pol II) by the ubiquitin-proteasome machinery.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PM01183 affects the inflammatory microenvironment, with selective apoptotic-inducing effect on tumor-associated macrophages, and specific inhibition of inflammatory cytokines production [4]. Strong preclinical antitumor activity was observed in cisplatin-resistant epithelial ovarian cancer models [5]. 35%) were the main safety findings for PM01183 [6].…”
Section: Resultsmentioning
confidence: 99%
“…When those PDX models were treated with carboplatin and paclitaxel, there was a significant decrease in tumor volume and mitotic index [22]. A decrease of 40% of tumor volume after treatment with cisplatin alone was seen in orthotopic models developed by Vidal et al when tumor was directly implanted into the ovary [32].…”
Section: Cytotoxic Chemotherapy In the Ovarian Pdx Modelmentioning
confidence: 97%